Shading Influence of Stand Sengon (Paraserianthes falcataria (L.) Nielsen) on Growth Porang Plants (Amorphophallus onchophyllus) - Wijayanto, Nurheni; pratiwi, Emma (Journal of Tropical Silviculture, 2011)
Sengon have a light canopy. Porang plant is resistant shade plants. So that these plants can be incorporated in the system agrofrestry. The purpose of this study was to examine the influence of shading intensity on plant growth porang. The experimental design used randomized block design. Group consists of stands with a canopy sengon 30% and 80%. Porang plants fertilized with organic fertilizer. Porang plant parameters were observed: plant height, crown diameter, tuber fresh weight, dry weight of canopy, root dry weight, bulb diameter, and biomass.The results showed that the intensity of the shade 30% performed better than the 80% shading intensity on plant growth porang.  Therefore, it stands 30% sengon shade plants porang potential for development.